Unlocking Fraud Prevention in Village Fund Management: Causal Factor Perspective - Balkis, Rafni; Komala, Lenda (Research of Accounting and Governance, 2024)
This study sought to ascertain the impact of person morality, compensation suitability, village apparatus competency, and accountability on the partial prevention of fraudulent village fund administration. The methodology employed in the research is a quantitative research method and uses primary data, namely in the village in Babelan District, Bekasi, West Java. The sample used was 50 respondents in the 2022 period through purposive sampling method. The With a significance threshold of 5%, the multiple linear regression analysis methodology is employed. The study's findings partially indicate that while accountability has a significant negative impact on preventing fraud in village fund management, village apparatus competence, compensation suitability, and individual morality have positive and significant effects on this variable. Implications for managers in this research All village fund management procedures, including the creation of financial reports and reporting on the usage of funds, must be carried out honestly, according to management funds, Conduct periodic performance evaluations to ensure that village officials have adequate and continuously improving capabilities, Establish a fair compensation scheme and in accordance with the responsibilities and workload of village officials.